2013
DOI: 10.1039/c3nr00549f
|View full text |Cite
|
Sign up to set email alerts
|

Doped semiconductor nanocrystal based fluorescent cellular imaging probes

Abstract: Doped semiconductor nanocrystals such as Mn doped ZnS, Mn doped ZnSe and Cu doped InZnS, are considered as new classes of fluorescent biological probes with low toxicity. Although the synthesis in high quality of such nanomaterials is now well established, transforming them into functional fluorescent probes remains a challenge. Here we report a fluorescent cellular imaging probe made of high quality doped semiconductor nanocrystals. We have identified two different coating approaches suitable for transforming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…Q-dots may additionally be doped with other metal ions to give, for example, brightly fluorescent Mn-doped ZnS, Mn-doped ZnSe, or Cu-doped InZnS particles (10-80 nm in diameter) which represent a new class of fluorescent nanoparticles with low toxicity. 120 Aside from Q-dots composed of Zn(II), Cd(II), sulfide and selenide there are numerous other kinds of such particles. It is difficult to keep track with the variety of materials that have been presented in recent years.…”
Section: Metal Chalcogenide Quantum Dots (Classical Q-dots)mentioning
confidence: 99%
“…Q-dots may additionally be doped with other metal ions to give, for example, brightly fluorescent Mn-doped ZnS, Mn-doped ZnSe, or Cu-doped InZnS particles (10-80 nm in diameter) which represent a new class of fluorescent nanoparticles with low toxicity. 120 Aside from Q-dots composed of Zn(II), Cd(II), sulfide and selenide there are numerous other kinds of such particles. It is difficult to keep track with the variety of materials that have been presented in recent years.…”
Section: Metal Chalcogenide Quantum Dots (Classical Q-dots)mentioning
confidence: 99%
“…Mn-or Cu-doped Zn chalcogenide QDs, whichd on ot contain heavy metal ions, could potentially serve as fluorescent imaging probesw ith reduced toxicity. [116] Although silicon-based QDs are biocompatible and potentially biodegradable, their clinicala pplicationi s still questionable. Erogbogbo et al demonstrated that silicon QDs could be safely used at high doses (minimal cytotoxicity both in vitro and in vivo).…”
Section: In Vivo Toxicitymentioning
confidence: 99%
“…However, presence of heavy metals in their composition limits their extensive and wider application in various in vivo therapeutic and clinical applications . Thus, alternative fluorescent nanoparticles similar to quantum dots are under intense investigation that includes carbon, silicon, doped semiconductor, and gold clusters …”
Section: Introductionmentioning
confidence: 99%